Keabsahan Transaksi Jual Beli Yang Dilakukan Oleh Tunanetra Menurut Mazhab Hanafi Dan Mazhab Syafi’i - Muhammad Siraji; Imam Alfiannor; Ruslan (Interdisciplinary Explorations in Research Journal, 2023)
Abstract The scholars state that the original law in Muamalah is permissible, unless there is evidence that forbids it. Thus, the original law in buying and selling is halal. However, to be considered valid, buying and selling transactions must fulfill the pillars and conditions in accordance with the views of the madhhabs adopted. The Hanafi Mazhab and the Shafi'i Mazhab have different views on the pillars and conditions of buying and selling. One of the striking differences is related to visual impairment, especially for blind people. The Hanafi Mazhab considers the sale and purchase transactions of blind people to be valid, while the Shafi'i Mazhab states that it is not valid because it involves the element of gharar. This research aims to find out why the Hanafi and Shafi'i Mazhabs differ in their opinions in punishing sale and purchase transactions carried out by the blind. The type of research that will be used in this research is descriptive normative legal research through a comparative approach. The results of this study found that the Hanafi Mazhab is of the opinion that the sale and purchase transactions carried out by the blind are valid on the condition that there is a khiyar nature plus the hadith that Umar bin Khattab saw that Hibban bin Munqidz was a blind man who was given khiyar rights for 3 days to transact buying and selling for blind buyers, and the existence of Ijmak Sukuti at the time of the companions, namely there is no prohibition on buying and selling transactions carried out by the blind. This is different from the Shafi'i school of thought which argues that the sale and purchase transactions carried out by the blind are not valid according to their shahih school of thought because of the hadith evidence that the prophet Muhammad SAW prohibited buying and selling that contained elements of deception because in the sale and purchase transactions carried out by the blind there was a great deception. Keywords: Buying and Selling, Visually Impaired, Hanafi Mazhab, Shafi'i Mazhab Abstrak Para ulama menyatakan bahwa hukum asal dalam Muamalah adalah boleh, kecuali ada dalil yang mengharamkannya. Dengan demikian, hukum asal dalam jual beli adalah halal. Namun, untuk dianggap sah, transaksi jual beli harus memenuhi rukun dan syarat sesuai dengan pandangan mazhab yang dianut. Mazhab Hanafi dan Mazhab Syafi’i memiliki pandangan berbeda mengenai rukun dan syarat jual beli. Salah satu perbedaan mencolok adalah terkait keterbatasan penglihatan, khususnya pada orang tunanetra. Mazhab Hanafi menganggap transaksi jual beli orang tunanetra sah, sementara Mazhab Syafi’i menyatakan bahwa tidak sah karena melibatkan unsur gharar.maka penelitian ini bertujuan untuk mengetahui mengapa mazhab Hanafi dan Syafi’i berbeda pendapat dalam menghukumi transaksi jual beli yang dilakukan oleh tunanetra. Jenis penelitian yang akan digunakan dalam penelitian ini adalah penelitian hukum normatif bersifat deskriptif melalui pendekatan komparatif. Hasil penelitian ini didapati bahwa Mazhab Hanafi berpendapat sah transaksi jual beli yang dilakukan oleh tunanetra dengan syarat adanya khiyar sifat ditambah adanya hadits bahwa Umar bin Khattab yang melihat bahwa Hibban bin Munqidz seorang buta yang diberikan hak khiyar selama 3 hari untuk bertransaksi jual beli untuk pembeli yang tunanetra,dan adanya Ijmak Sukuti pada zaman sahabat yaitu tidak adanya larangan transkasi jual beli yang dilakukan oleh Tunanetra. berbeda dengan mazhab Syafi’i yang berpendapat tidak sah transaksi jual beli yang dilakukan oleh tunanetra menurut pendapat shahih mazhab mereka karena adanya dalil hadits bahwa nabi Muhammad SAW melarang jual beli yang mengandung unsur tipuan karena dalam transaksi jual beli yang dilakukan oleh tunanetra terdapat tipuan yang besar. Kata kunci: Jual Beli, Tunanetra, Mazhab Hanafi, Mazhab Syafi’i This is an open access article under the CC BY-NC-SA license.